Sudoscan in the evaluation and follow-up of patients and carriers with TTR mutations: experience from an Italian Centre. (2nd October 2018) - Luigetti, Marco; Bisogni, Giulia; Romano, Angela; Di Paolantonio, Andrea; Barbato, Francesco; Primicerio, Giulia; Rossini, Paolo Maria; Servidei, Serenella; Sabatelli, Mario
Abstract: Objective: To evaluate the utility of Sudoscan as possible marker of disease progression and disease onset in a cohort of hereditary ATTR amyloidosis (hATTR amyloidosis) polyneuropathy patients and carriers. Patients and methods: We regularly performed different clinical scales, nerve conductions studies (NCS), and Sudoscan on a cohort of hATTR amyloidosis patients and carriers from a single centre of central Italy, a non-endemic area, in the last 2 years. Results : About 18 hATTR amyloidosis patients and 8 asymptomatic carriers were enrolled. All patients had a neuropathy affecting large fibres, small fibres or both. Two subjects developed symptoms and neurophysiological alterations during follow-up. Sudoscan data from hand and feet inversely correlated with neuropathy severity and with disease duration. Moreover, global disease status, expressed by Kumamoto scale also inversely correlated with Sudoscan values. Conclusions: We confirmed that Sudoscan is a reliable marker of disease progression in late-onset hATTR amyloidosis patients and we suggest its possible utility in early detection of disease in this population.